2018
DOI: 10.1016/j.ijheh.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Home proximity to flower plantations and higher systolic blood pressure among children

Abstract: Proximity of homes to flower plantations and greater plantation areas within 150 m from homes were associated with higher systolic BP, independent of cholinesterase activity. This suggests that non-cholinesterase inhibitor pesticide drift from agricultural plantations may be sufficient to induce physiologic changes on children living nearby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Children growing up in the agricultural Pedro Moncayo County, have an increased risk for exposure to agrochemicals, including cholinesterase inhibitor insecticides, compared to urban children. A single measure of AChE activity in this setting is an indicator of exposure to cholinesterase inhibitors as lower values have been observed among a) children living with floricultural workers, in particular with those with greater pesticide "take-home" pathways; b) children living near pesticide spray sites; and c) children examined sooner after the end of a pesticide spray season compared to those examined later (Suarez-Lopez et al, 2018. To our knowledge, this is the first epidemiologic study to describe an association between depressive symptoms and pesticide exposures in adolescents using an exposure biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Children growing up in the agricultural Pedro Moncayo County, have an increased risk for exposure to agrochemicals, including cholinesterase inhibitor insecticides, compared to urban children. A single measure of AChE activity in this setting is an indicator of exposure to cholinesterase inhibitors as lower values have been observed among a) children living with floricultural workers, in particular with those with greater pesticide "take-home" pathways; b) children living near pesticide spray sites; and c) children examined sooner after the end of a pesticide spray season compared to those examined later (Suarez-Lopez et al, 2018. To our knowledge, this is the first epidemiologic study to describe an association between depressive symptoms and pesticide exposures in adolescents using an exposure biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations in neurobehavioral performance may also be present at greater distances but the limited statistical power of our study to detect smaller differences precluded us from assessing this further. In previous analyses of the ESPINA study, we observed positive associations between residential distances to flower crops and AChE activity, with the lowest AChE levels observed among children living within 232m of a greenhouse floricultural crop (Suarez-Lopez et al, 2018). This supports the construct of residential distance to flower plantations as a pathway of exposure to pesticides Furthermore, we previously observed that children living closer to flower crops had higher systolic blood pressures, which indicates that additional physiologic processes may be affected among children living near pesticide spray sites (Suarez-Lopez et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…Residential distance from treated floricultural crops was used as a proxy for childhood exposure to floricultural pesticides. Though a crude exposure assessment, the use of this exposure metric is supported by the existing literature and validated within our study population (Suarez-Lopez et al, 2018). Prevailing winds were not accounted for in the present analyses.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations